Prostaglandin E2 secreted from feline adipose tissue-derived mesenchymal stem cells alleviate DSS-induced colitis by increasing regulatory T cells in mice - Ju-Hyun AN; Woo-Jin SONG; Qiang LI; Sang-Min KIM; Ji-In YANG; Min-Ok RYU; A Ryung NAM; Dong Ha BHANG; Yun-Chan JUNG; Hwa-Young YOUN (BMC Veterinary Research, 2018)
Abstract Background Inflammatory bowel disease (IBD) is an intractable autoimmune disease, relatively common in cats, with chronic vomiting and diarrhea. Previous studies have reported that mesenchymal stem cells (MSCs) alleviate inflammation by modulating immune cells. However, there is a lack of research on cross-talk mechanism between feline adipose tissue-derived mesenchymal stem cells (fAT-MSCs) and immune cells in IBD model. Hence, this study aimed to evaluate the therapeutic effects of fAT-MSC on mice model of colitis and to clarify the therapeutic mechanism of fAT-MSCs. Results Intraperitoneal infusion of fAT-MSC ameliorated the clinical and histopathologic severity of colitis, including body weight loss, diarrhea, and inflammation in the colon of Dextran sulfate sodium (DSS)-treated mice (C57BL/6). Since regulatory T cells (Tregs) are pivotal in modulating immune responses and maintaining tolerance in colitis, the relation of Tregs with fAT-MSC-secreted factor was investigated in vitro. PGE2 secreted from fAT-MSC was demonstrated to induce elevation of FOXP3 mRNA expression and adjust inflammatory cytokines in Con A-induced feline peripheral blood mononuclear cells (PBMCs). Furthermore, in vivo, FOXP3+ cells of the fAT-MSC group were significantly increased in the inflamed colon, relative to that in the PBS group. Conclusion Our results suggest that PGE2 secreted from fAT-MSC can reduce inflammation by increasing FOXP3+ Tregs in mice model of colitis. Consequently, these results propose the possibility of administration of fAT-MSC to cats with not only IBD but also other immune-mediated inflammatory diseases.